Pandangan Fikih Terhadap Pembatasan Minimal Usia Perkawinan - Hamdan Arief Hanif; Chaula Luthfia (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Law Number 16 of 2019 is a law that the main point is to regulate new regulation regarding the minimum age for marriage. Previously, the minimum age for marriage was 19 years for men and 16 years for women. Then this minimum limit was changed to 19 years for both. In Islam, the marriage contract (‘aqd) is a contract that is full of religious activities. However, in Islamic law or fiqh, there is no any evidence that clearly regulates the minimum age for marriage. This paper aims to analyze the rules for limiting the minimum age for marriage from a fiqh perspective. This type of research is normative-empirical legal research with a conceptual approach. The results of the study show that normatively, changes of Law Number 16 of 2019 have been in line with the provisions and principles in fiqh. However, in practice, this research proves that the changing of this law is not fully in accordance with the purposes and benefits in fiqh.